Termination of Employment Relationships during the Covid-19 Pandemic in East Kalimantan - Tuti Wediawati; Tri Utari (Budapest International Research and Critics University, 2021)
Termination of employment in companies is usually done for various reasons, one of which is efficiency. Efficiency can be due to company closures or companies experiencing losses. By labour law in Indonesia, companies cannot terminate employment (PHK) without specific reasons for their employees. Layoffs must be based on solid and valid reasons, as stated in the Job Creation Law No. 11 of 2020, Chapter IV Manpower, and point 42 regarding the insertion of Article 154A into the Manpower Act No. 13 of 2003. This was forced to done by several companies due to reasons efficiency due to the impact of covid 19 that hit the world, including Indonesia and Kalimantan Eastin particular. The purpose of this study was to find out how and to what extent the terms of Labor Relations occurred in East Kalimantan Province, especially during the Covid 19 Pandemic. The data source was secondary data originating from various media that reviewed cases of layoffs that occurred in East Kalimantan and some information from related agencies, especially the East Kalimantan Provincial Manpower Office, published by several local media. This research is secondary data analysis using qualitative descriptive analysis.